2016
DOI: 10.1093/neuonc/now166
|View full text |Cite
|
Sign up to set email alerts
|

Cancers of the brain and CNS: global patterns and trends in incidence

Abstract: Important regional variations in brain and CNS cancers exist, and given an increasing burden and risk worldwide, there is a need for further etiological research that focuses on the elucidation of environmental risk. The trends are sufficiently complex and diffuse, however, to warrant a cautious approach to interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
123
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 47 publications
(32 reference statements)
15
123
1
7
Order By: Relevance
“…A previous study based on English cancer incidence data and a novel causal inference framework based on synthetic counterfactuals indicated that the observed increase in malignant neoplasms in the temporal lobe between 1985-2014 was in agreement with mobile phone use as an important causal factor, but that for GBM, despite its incidence increasing over time as well, this did not deviate from expected, counterfactual, trends , de Vocht, 2017). Similar trends have been observed elsewhere (Ho et al, 2014, Kim et al, 2015, Ostrom et al, 2014, Zada et al, 2012, and improvements in diagnostics techniques, especially in the elderly, is generally considered the main explanation for the observed increase in incidence, while genetic risk factors and ionizing radiation exposure are known to increase the risk and allergic conditions appear to decrease it (Miranda-Filho et al, 2017) . A variety of other potential contributing factors have also been hypothesized to additionally explain these patterns, including hormonal contraceptives, hormone replacement therapy, statins, certain infections, a variety of occupational exposures, vitamin D, alcohol, height, BMI, as well as non-ionizing radiation including RF from mobile phones (Kim et al, 2015, Miranda-Filho et al, 2017, Philips et al, 2018.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…A previous study based on English cancer incidence data and a novel causal inference framework based on synthetic counterfactuals indicated that the observed increase in malignant neoplasms in the temporal lobe between 1985-2014 was in agreement with mobile phone use as an important causal factor, but that for GBM, despite its incidence increasing over time as well, this did not deviate from expected, counterfactual, trends , de Vocht, 2017). Similar trends have been observed elsewhere (Ho et al, 2014, Kim et al, 2015, Ostrom et al, 2014, Zada et al, 2012, and improvements in diagnostics techniques, especially in the elderly, is generally considered the main explanation for the observed increase in incidence, while genetic risk factors and ionizing radiation exposure are known to increase the risk and allergic conditions appear to decrease it (Miranda-Filho et al, 2017) . A variety of other potential contributing factors have also been hypothesized to additionally explain these patterns, including hormonal contraceptives, hormone replacement therapy, statins, certain infections, a variety of occupational exposures, vitamin D, alcohol, height, BMI, as well as non-ionizing radiation including RF from mobile phones (Kim et al, 2015, Miranda-Filho et al, 2017, Philips et al, 2018.…”
Section: Introductionsupporting
confidence: 79%
“…Similar trends have been observed elsewhere (Ho et al, 2014, Kim et al, 2015, Ostrom et al, 2014, Zada et al, 2012, and improvements in diagnostics techniques, especially in the elderly, is generally considered the main explanation for the observed increase in incidence, while genetic risk factors and ionizing radiation exposure are known to increase the risk and allergic conditions appear to decrease it (Miranda-Filho et al, 2017) . A variety of other potential contributing factors have also been hypothesized to additionally explain these patterns, including hormonal contraceptives, hormone replacement therapy, statins, certain infections, a variety of occupational exposures, vitamin D, alcohol, height, BMI, as well as non-ionizing radiation including RF from mobile phones (Kim et al, 2015, Miranda-Filho et al, 2017, Philips et al, 2018. This paper further expands on previous analyses and utilises the strengths of the Bayesian causal inference work using synthetic counterfactuals to explore the likelihood of mobile phone use as the important putative factor explaining the increases in the incidence of GBM in different anatomic brain regions and for specific malignant (other than GBM) and benign (acoustic neuroma and meningioma) subtypes in the temporal lobe specifically (based on the results from the previous study (de Vocht, 2016)).…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…A decreasing trend in the incidence of malignant brain tumors was reported in both males and females between 1993 and 2007 in Japan [Miranda‐Filho et al, ]. In that analysis, the age‐adjusted incidence of subjects aged 15 years old and over was shown.…”
Section: Discussionmentioning
confidence: 96%